2007
DOI: 10.1677/joe.1.07059
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated acidic serine–aspartate-rich MEPE-associated motif peptide from matrix extracellular phosphoglycoprotein inhibits phosphate regulating gene with homologies to endopeptidases on the X-chromosome enzyme activity

Abstract: Inactivating PHEX (phosphate regulating gene with homologies to endopeptidases on the X chromosome) mutations cause X-linked hypophosphatemia in humans and mice (Hyp) through overproduction of fibroblast growth factor 23 (FGF23) a phosphaturic factor, by osteocytes. Matrix extracellular phosphoglycoprotein (MEPE) is also elevated in Hyp and other hypophosphatemic disorders. In addition, the administration of an ASARM (acidic serineaspartate rich MEPE-associated motif) peptide derived from MEPE causes phosphatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 35 publications
12
86
2
Order By: Relevance
“…Studies of rodents showed that 1,25(OH) 2 D 3 inhibits MEPE production by osteoblasts 19 and that MEPE stimulates FGF-23 production in bone marrow stromal cells. 20 Indeed, a model of the complex interplay among FGF-23, 1,25(OH) 2 D 3 , and MEPE was described by Rowe and colleagues. Increased serum concentrations of MEPE have been reported in patients with X-linked hypophosphatemic rickets and in the Hyp mouse model of this disorder, 22 and MEPE was originally proposed as the factor responsible for hypophosphatemia, phosphaturia, and defective mineralization characteristic of X-linked hypophosphatemic rickets; however, a study of Hyp mice crossed onto a MEPE null background showed that MEPE is not the phosphaturic factor in this mouse model, because hypophosphatemia persisted.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of rodents showed that 1,25(OH) 2 D 3 inhibits MEPE production by osteoblasts 19 and that MEPE stimulates FGF-23 production in bone marrow stromal cells. 20 Indeed, a model of the complex interplay among FGF-23, 1,25(OH) 2 D 3 , and MEPE was described by Rowe and colleagues. Increased serum concentrations of MEPE have been reported in patients with X-linked hypophosphatemic rickets and in the Hyp mouse model of this disorder, 22 and MEPE was originally proposed as the factor responsible for hypophosphatemia, phosphaturia, and defective mineralization characteristic of X-linked hypophosphatemic rickets; however, a study of Hyp mice crossed onto a MEPE null background showed that MEPE is not the phosphaturic factor in this mouse model, because hypophosphatemia persisted.…”
Section: Discussionmentioning
confidence: 99%
“…The following biochemical parameters were measured because of their novelty or correlation with bone parameters in cross-sectional prior studies: serum parathyroid hormone (PTH; commonly used to assess bone turnover abnormalities, which have been shown to be associated with changes in bone volume) (12), bone-specific alkaline phosphatase (BSAP) and procollagen type 1 N-terminal propeptide (P1NP; which are markers of osteoblastic activity) (13,14), tartrate-resistant acid phosphatase-5b (TRAP-5b; a marker of osteoclastic activity) (15), sclerostin (a protein produced by osteocytes [16,17] and expressed at bone formation sites [18,19]), Dickkopf-1 (DKK-1; found in bone and other tissues [20], and like sclerostin, it leads to increased bone formation and bone volume when knocked out) (21,22), and fibroblast growth factor 23 (FGF23; involved in mineral metabolism with a role in bone mineralization/remodeling) (23)(24)(25). In addition, serum calcium and phosphorus were measured.…”
Section: Determinations Of Blood Parametersmentioning
confidence: 99%
“…Both systemic factors and local bone-derived factors seem to regulate FGF23 promoter activity (31). In this regard, circulating FGF23 levels are regulated by phosphate (32) and 1,25(OH) 2 D (31) as well as by the Phex endopeptidase located in osteocytes (7) and the SIBLING extracellular matrix proteins DMP1 (18,33) and MEPE (34). Phosphate loading in mice increases FGF23 levels (32), although the data in humans are conflicting (35)(36)(37).…”
Section: Regulation Of Fgf23mentioning
confidence: 99%
“…The targeted deletion of DMP1 increases FGF23 expression in osteocytes, leading to increased circulating levels (18). In contrast, MEPE administration causes phosphaturia, possibly by increasing FGF23 levels (34,40). In activating mutations of Phex, an endopeptidase that is located in osteocytes also results in increased transcription of FGF23 and elevated circulating levels (7).…”
Section: Regulation Of Fgf23mentioning
confidence: 99%